Diseño Lógico de un protocolo con esquema de seguridad para una Red Móvil Urbana - Alvarez Ramirrez, Bryan Frank William (2013)
When safety and mobility needs in communications, depending of cables is restriction_x000D_ to achieve full freedom of movement. To overcome the restrictions imposed by the cable,_x000D_ wireless communications become an alternative to conventional communication systems._x000D_ There is no doubt that wireless communications are booming and have achieved in recent_x000D_ years the strength maturity and standardization needed to become a real alternative_x000D_ to wired networks, but in these times where computer crime undermines the security hereby_x000D_ we nd it necessary to propose an alternative solution where mobile networks play a_x000D_ role safely to an urban area. We may also note in recent years a sharp decline in economic_x000D_ cost of hardware necessary for wireless communications. That is why users or future users_x000D_ of this technology are interested in to evaluate the performance of these devices, so you_x000D_ can choose to use safely and is therefore the interest of the latter factor which encourages_x000D_ us to provide an alternative solution for urban mobile network safe._x000D_ There are two types of wireless networks: Those which are constituted, besides wireless_x000D_ devices, by forming a part infrastructure or extension thereof (with network infrastructure),_x000D_ and those lacking this part and are constituted by a set of devices wireless phones,_x000D_ which can connect dynamically and arbitrarily among them, also in charge of the routing_x000D_ of all messages and information control (Ad-Hoc Networks). This last will be in what we'll_x000D_ work._x000D_ Wireless networks have many applications, such as portable o ce: professionals who_x000D_ are continuously moving in their work and need to use their electronic devices to send and_x000D_ receive phone calls, faxes, email, they can access to remote computers, read and modify_x000D_ les in these computers all this in a safe, where data traveling on the network is not_x000D_ subject to vulnerability._x000D_ The objective of this study is to propose a logical diagram of a security protocol scheme_x000D_ for urban mobile network by using Ad-Hoc wireless networks using as representative_x000D_ of proactive routing OLSR (Optimized Link State Routing)_x000D_ The security we propose for this routing protocol will through three mechanisms which_x000D_ employ solutions developed and implemented in various projects such as certi cation,_x000D_ encryption, which were added to the protocol to make it a secure OLSR._x000D_ vii_x000D_ viii_x000D_ The work is organized into eight chapters. Chapter 1 provides an introduction and_x000D_ problematic reality. Chapter 2 presents the theoretical framework introduced routing protocols,_x000D_ making a study of OLSR and AODV. Chapter 3 explains the design of the protocol_x000D_ scheme. Chapter 4 presents the proposed logical design mediantes the three stages which_x000D_ are neighbor discovery, authentication and messaging neighbors. In Chapter 5 the design_x000D_ details of the proposed scheme. Chapter 6 shows the analysis and results of the proposed_x000D_ design. In Chapter 7 of the paper presents the conclusions and recommendations as well_x000D_ as a glossary of terms and nally, the presented bibliography